Digestibilidade aparente de ingredientes com certificação de origem orgânica e sua inclusão na alimentação de juvenis de tilápia do Nilo - Freitas, Jakeline Marcela Azambuja de (2012)
This study was carried out aimed to determine the energy and protein apparent digestibility coefficients of organic soybean meal, wheat meal, corn and whole wheat for Nile tilapia and the evaluation of productive performance of fish fed with food supplemented organically certified energy plant source. In digestibility trial were utilized 100 juveniles of Nile tilápia with 100 g average weight randomly assigned into five 200 L appropriate for feces collect tanks. To evaluate digestibility coefficients of ingredients in study, five diets were prepared, one reference and four tests included 70% of the reference diet and 30% of the test food. All diets were marker with 0,1% chromic oxide. The randomized Latin square desing used containing five treatments and five repetitions. The digestible protein (%) and energy (kcal kg-1) of organic soybean meal, wheat meal, corn and wheat were: 39,69 and 3630,85; 14,32 and 3348,09; 7,54 and 3100,45; 16,29 and 3571,06; respectively. To evaluate of productive performance, chemical composition and blood biochemical parameters of juveniles Nile tilápia fed with diets containing as energy source the wheat meal, corn and whole wheat with organic origin certification and mixed all sources (wheat meal + corn + whole wheat), 300 juveniles Nile tilápia were randomly assigned into 20 experimental tanks (500 L). The entirely casualized delineation used containing four treatments and five repetitions. The animals with 10,39 ± 0,98 g average weight and 8,10 ± 0,44 cm total length, were fed four times a day, at apparent satiation. At the end experimental period were evaluate parameters of final weight, total length, weight gain, feed conversion, survival, specific growth rate and factor condition of animals subjected to different diets. The biochemical analysis of the blood comprised the determination levels of glucose (mg dL-1), triglycerides (mg dL-1) and total protein (mg dL-1), whereas for centesimal composition of the carcass were evaluated proportions of humidity, lipids, protein and ash. The analysis of variance showed significant influence for the parameters of final weight, weight gain, food conversion, specific growth rate and in the lipidic percentage of the carcass. The best results for weight gain were obtained for animals fed on food containing organic corn (145,13 g) and a mixture of all the sources evaluated (143,90 g). The same can be assigned for the specific growth rate (4,50% dia-1 for both). The best results for food conversion index were observed for animals that received food containing organic whole wheat (0,74) and a mixture of different sources (0,81). Analogue behavior was verified in relation to the deposition of fat in the carcass, with the best results obtained for wheat (5,34%) and mixed (5,60%). Diets containing as energetic source a mixture of organic wheat bran + corn + whole wheat, provided optimum performance, lower deposition of fat in the carcass and not cause changes in blood biochemical parameters and maintains the healthiness of juveniles Nile tilápia